Gruesomeness conveys formidability: Perpetrators of gratuitously grisly acts are conceptualized as larger, stronger, and more likely to win. Issue 5 (11th June 2020) - Scrivner, Coltan; Holbrook, Colin; Fessler, Daniel M. T.; Maestripieri, Dario
Abstract: While associated with extreme terrorist organizations in modern times, extensive accounts of grisly acts of violence exist in the archeological, historical, and ethnographic records. Though reasons for this dramatic form of violence are multifaceted and diverse, one possibility is that violence beyond what is required to win a conflict is a method by which violent actors communicate to others that they are formidable opponents. The formidability representation hypothesis predicts that formidability is cognitively represented using the dimensions of envisioned bodily size and strength. We tested the informational ramifications of gruesome acts using two vignette studies depicting individuals who either did or did not grievously damage the corpse of a deceased foe. Participants rated the individual's height, bodily size, and strength, as well as his aggressiveness, motivation, and the capacity to vanquish opponents in future conflicts. Results indicate that, as predicted, committing gruesome acts of violence enhances perceptions of formidability as measured both by envisioned bodily size and strength and expectations regarding the outcomes of agonistic conflicts. Moreover, the gruesome actor was perceived as more aggressive and more motivated to overcome his enemies, and this mediated the increase in conceptualized size and strength. These results both provide further evidence for the formidability representation hypothesis and support the thesis that overtly grisly violence is tactically employed, in part, because it conveys information about the perpetrator's formidability.